AI-ASSISTED SPEAKING PRACTICE MODEL: INTEGRATING CHATGPT INTO COMMUNICATIVE LANGUAGE TEACHING FOR EFL LEARNERS - Weran, Yohana; Lailatus Sa'adah (Pedagogic Research-Applied Literacy Journal, 2025)
The rapid development of Artificial Intelligence (AI) has created new opportunities for enhancing English as a Foreign Language (EFL) instruction, particularly in speaking skills. This conceptual study proposes an AI-assisted speaking practice model that integrates ChatGPT into the Communicative Language Teaching (CLT) framework. The model aims to provide learners with interactive, context-rich speaking experiences through AI-generated prompts, role-play simulations, and real-time feedback. Drawing on principles of CLT and task-based learning, the proposed model consists of three main stages: pre-task preparation, AI-mediated communicative tasks, and post-task reflection and feedback. Potential benefits include increased learner motivation, expanded speaking opportunities, personalized practice, and the development of fluency and accuracy in authentic communicative contexts. However, challenges such as digital literacy, potential overreliance on AI, and infrastructure limitations must be addressed to ensure effective implementation. This study offers a practical framework for integrating generative AI tools into EFL speaking instruction and provides recommendations for future empirical research on its classroom application.